Suspected poisoning in beef cattle from ingestion of Prosopis nigra pods in north-western Argentina - Micheloud, Juan Francisco; Colque Caro, Luis Adrian; Cholich, Luciana Andrea; Martínez, Olga Gladys; Gimeno, Eduardo Juan (Elsevier, 2019)
The aim of this paper was to present the first report of Prosopis nigra poisoning of cattle in Argentina. Outbreaks occurred in five farms located in Salta and Santiago del Estero provinces. All animals were examined, euthanized and necropsied. Clinical signs included tongue protrusion, twitches and tremors of muscles of mastication, weight loss and lethargy. Severe atrophy of the masseter, buccinator and lingual muscles was observed, along with neuronal vacuolation in the nuclei of the trigeminal, facial, and hypoglossus nerves. These findings and the clinical signs are consistent with results obtained in animals, spontaneously and experimentally intoxicated with Prosopis juliflora in previous studies. Several species of this genus are native to Argentina. Farmers should be warned about the suspected toxicity by Prosopis nigra, since this species has wide geographical distribution in the country